DocToBib: an expanding project of video research training tutorials for interns, health students and practicians, three years later (Journal of EAHIL, 2019)
DocToBib is a project carried out by librarians all over France to create video tutorials on research training in the medical field. This is an update on how the project evolved since 2015, on the topic of video format, collaboration between librarians, communication and practical uses of the tutorials.